1989
DOI: 10.1002/1097-0142(19891015)64:8<1753::aid-cncr2820640833>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma presenting as bone metastasis

Abstract: In a consecutive series of 395 patients with pathologically verified hepatocellular carcinoma, 20 patients (5%) had bone metastasis at initial presentation. Of these, 16 were men and four women ranging from 26 to 64 years of age (median, 50 years). The age, sex, hepatitis B surface antigen seropositivity, alpha-fetoprotein level, and frequency of associated cirrhosis were not statistically different from those in patients without initial bone metastasis. Initial presentation was usually the result of spinal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 25 publications
(1 reference statement)
10
47
1
Order By: Relevance
“…HCC metastases to bone are seen in 3.0-10.0% of HCC patients. [5][6][7][8][9][10] The common sites are vertebra, pelvis, ribs and skull. 11 The bony lesions due to metastatic HCC in our case was osteolytic.…”
Section: Discussionmentioning
confidence: 99%
“…HCC metastases to bone are seen in 3.0-10.0% of HCC patients. [5][6][7][8][9][10] The common sites are vertebra, pelvis, ribs and skull. 11 The bony lesions due to metastatic HCC in our case was osteolytic.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BMs in HCC patients has been reported to be relatively low; 2%-12.9% in clinical studies, and 7.3%-38.5% in patients with extrahepatic metastases (Table 1) [2, 3,5,[13][14][15][16] . However, BM incidences of 10.2% and 12.9% were reported by Katyal et al [15] and Fukutomi et al [3] , respectively, which are higher than previously reported rates.…”
Section: Incidence Of Bmsmentioning
confidence: 99%
“…The lower-thoracic and lumbar vertebrae are common sites for vertebral BMs [18] . The reported incidence of skull metastases varies widely; 3.5%-30% [4,7,8,14] . Radiographically, typical BMs from HCC appear as expansible, destructive findings with large soft-tissue masses [13] .…”
Section: Radiological Featuresmentioning
confidence: 99%
See 2 more Smart Citations